A high-strength polyimide aerogel fiber and preparation method thereof
By introducing triethylamine and crosslinking agent in the spinning process of polyamide fibers and using a pure water solidification bath to form polyimide aerogel fibers with a three-dimensional network structure, the cost and environmental problems of using organic solvents in the spinning process of traditional fibers are solved, and fiber materials with high strength, low thermal conductivity and good spinning are achieved.
Patent Information
- Application Number
- CN202210848443.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-19
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-07-19
AI Technical Summary
Traditional polyimide fibers require the use of organic solvents as a solidification bath during spinning, which leads to high costs and serious environmental pollution, and the high concentration and dense structure of the spinning liquid lead to high density and poor spinning properties.
By introducing triethylamine and crosslinking agent, the water solubility of the polyamic acid salt and the viscosity of the spinning liquid are improved. Pure water is used as a solidification bath to achieve a spinning liquid with low concentration, high viscosity and good spinning. Then solvent replacement and drying are carried out to form a polyimide aerogel fiber with a three-dimensional network structure.
Polyimide aerogel fibers with high strength, good toughness and low thermal conductivity have good spinning properties and are suitable for textiles, special clothing and industrial insulation fields. They have simple processes, easy raw materials, and can achieve large-scale production.
Smart Images

Figure CN115260571B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a fiber material and a preparation method thereof, and more particularly to a high-strength polyimide aerogel fiber and a preparation method thereof. Background Art
[0002] Human beings have a long history of using fiber materials. Natural fibers such as cotton, linen, silk, and wool, as well as synthetic fibers such as nylon, acrylic, and Teflon have always been important thermal insulation materials for humans. Although synthetic fiber materials were born relatively late, they have high performance, high strength, and high precision that natural fiber materials do not have. However, synthetic fiber materials do not have more advantages in terms of thermal insulation performance. The reason is that synthetic fibers spun using traditional methods do not have a three-dimensional network structure, have low porosity and specific surface area, and have no significant improvement in thermal insulation effect compared to natural fibers.
[0003] The thermal insulation performance of fiber mainly depends on the density, porosity, specific surface area and the number and size of voids in the fiber material. The smaller the density of the fiber material, the larger the porosity, the larger the specific surface area and the higher the air content in the material, the better the thermal insulation performance. Aerogel is considered to be a new generation of high-efficiency thermal insulation material due to its unique porous network structure, and can therefore be used as an alternative material for the new generation of synthetic fibers.
[0004] Polyimide materials have the high temperature resistance and corrosion resistance of inorganic materials, and the good mechanical properties of organic materials, and have gradually attracted attention in recent years. How to introduce the three-dimensional network structure of aerogel into polyimide fibers to synthesize polyimide aerogel fibers with high specific surface area and porosity, as well as good strength and elasticity to meet the needs of textiles is an important research direction in the field of thermal insulation. The realization of simple and continuous preparation of high-strength aerogel fibers represents a qualitative leap in the field of synthetic fiber thermal insulation.
[0005] The coagulation bath in traditional polyimide fiber wet spinning is usually a mixture of organic solvent and water. The purpose is to slow down the fiber coagulation speed and avoid the formation of a dense film on the fiber surface due to rapid solvent exchange. However, a slower coagulation speed means a longer coagulation time and coagulation bath size. At the same time, a large amount of organic solvent is required, which is costly and the post-processing process is complicated. Therefore, how to use pure water as a coagulation bath is a difficult problem. The concentration of traditional polyimide fiber spinning solution is relatively high, generally 15%-18% by mass. Coupled with its dense structure, it leads to a higher density. However, the viscosity of low-concentration spinning solution is low and the spinnability is poor. How to prepare a low-concentration, high-viscosity, good spinnability and stable spinning solution is another challenge. Summary of the invention
[0006] In view of the above content, the present invention provides a high-strength polyimide aerogel fiber and a preparation method thereof.
[0007] The present invention comprises the following two aspects:
[0008] In the first aspect, a high-strength polyimide aerogel fiber is characterized by having a three-dimensional network structure formed by cross-linking polyimide nanofibers, wherein the polyimide aerogel fiber has a tensile strength of 20-100 MPa, an elastic modulus of 800-1400 MPa, and a specific surface area of 100-300 m 2 / g, linear density is 15-25tex, thermal conductivity is 0.02-0.07W·m -1 ·K -1 , and has good spinnability.
[0009] In a second aspect, the present invention provides a method for preparing a polyimide aerogel fiber, characterized in that it comprises the following steps:
[0010] Step S1, preparing a polyamic acid solution;
[0011] Step S2, performing a pre-spinning treatment on the polyamic acid solution to obtain a polyamic acid salt spinning solution;
[0012] Step S3, spinning the polyamic acid salt spinning solution to obtain polyamic acid salt hydrogel fibers;
[0013] Step S4, subjecting the polyamic acid salt hydrogel fiber to solution replacement to obtain polyamic acid salt organogel fiber, and then subjecting the polyamic acid salt hydrogel fiber to chemical imidization in solution to obtain polyimide organogel fiber; and
[0014] Step S5, performing solvent replacement on the polyimide organogel fiber, and then freeze-drying or supercritical drying to obtain the polyimide aerogel fiber.
[0015] The present invention has at least one of the following beneficial effects:
[0016] The high-strength polyimide aerogel fiber provided by the present invention has a typical three-dimensional network structure, has low thermal conductivity and linear density, has high strength and good toughness, has good spinnability, and can be applied to the fields of textiles, special clothing, and industrial thermal insulation;
[0017] The preparation method of the high-strength polyimide aerogel fiber provided by the present invention adopts widely available raw materials, has a simple preparation process, mild reaction conditions, a controllable reaction process, a continuous process flow, fewer pre- and post-processing steps, and can realize large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1It is a cross-sectional morphology SEM image (left) and a local magnified SEM image (right) of the polyimide aerogel fiber of Example 1 of the present invention.
[0019] Figure 2 Shown is a schematic diagram of the polyimide aerogel fiber of Example 2 of the present invention lifting a weight of 100 g (left) and the fiber still showing a certain strength after being knotted (right). DETAILED DESCRIPTION
[0020] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the present invention, rather than all embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0021] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0022] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0023] The high-strength polyimide aerogel fiber according to the first aspect of the present invention is characterized by having a three-dimensional network structure formed by cross-linking polyimide nanofibers, and the polyimide aerogel fiber has a tensile strength of 20-100 MPa, an elastic modulus of 800-1400 MPa, and a specific surface area of 100-300 m 2 / g, linear density is 15-25tex, thermal conductivity is 0.02-0.07W·m -1 ·K -1 , and has good spinnability.
[0024] The method for preparing the polyimide aerogel fiber according to the second aspect of the present invention is characterized by comprising the following steps:
[0025] Step S1, preparing a polyamic acid solution;
[0026] Step S2, performing a pre-spinning treatment on the polyamic acid solution to obtain a polyamic acid salt spinning solution;
[0027] Step S3, spinning the polyamic acid salt spinning solution to obtain polyamic acid salt hydrogel fibers;
[0028] Step S4, subjecting the polyamic acid salt hydrogel fiber to solution replacement to obtain polyamic acid salt organogel fiber, and then subjecting the polyamic acid salt hydrogel fiber to chemical imidization in the solution to obtain polyimide organogel fiber;
[0029] Step S5, performing solvent replacement on the polyimide organogel fiber, and then freeze-drying or supercritical drying to obtain the polyimide aerogel fiber.
[0030] Furthermore, in the step S1, the polyamic acid solution is formed by polymerizing a dianhydride monomer and a diamine monomer in an organic solvent;
[0031] The dianhydride monomer is one or more selected from the group consisting of pyromellitic anhydride, biphenyltetracarboxylic anhydride, diphenyl ether tetracarboxylic anhydride, benzophenone tetracarboxylic anhydride, bisphenol A type dianhydride, oxydiphthalic anhydride, biphenyltetracarboxylic anhydride, and pyromellitic anhydride;
[0032] The diamine monomer is one or more selected from 4,4'-diaminodiphenyl ether, p-phenylenediamine, diphenylmethane diisocyanate, toluene diisocyanate, 4,4'-diaminobenzanilide, 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl, 2,2'-bis[4-(4-aminophenoxyphenyl)]propane, and bis(4-aminophenoxy)benzene;
[0033] The organic solvent is one selected from N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide and dimethylacetamide.
[0034] Furthermore, the pre-spinning treatment in step S2 includes:
[0035] Step S21, adding triethylamine to the polyamic acid solution to adjust the water solubility of the spinning solution;
[0036] Step S22, adding a crosslinking agent to the solution after step S21 to improve the spinnability of the spinning solution;
[0037] Step S23, performing vacuum degassing treatment on the solution after step S22 to obtain a polyamic acid salt spinning solution;
[0038] The cross-linking agent is one or more selected from 1,3,5-tris(4-aminophenoxy)benzene, bis[3-(trimethoxysilyl)propyl]amine, N1,N3,N5 tris(4-aminophenyl)benzene-1,3,5-tricarboxamide, tris(4-aminophenyl)amine, 2,4,6-tris(4-aminophenoxy)-1,3,5-triazine, 1,3,5-tris(4-aminophenyl)benzene, melamine and its derivatives.
[0039] Furthermore, in step S2, the mass concentration of polyamic acid salt in the polyamic acid salt spinning solution is 5-15wt%, the molar ratio of the dianhydride monomer, the diamine monomer and the cross-linking agent is (n+1) / n / m, wherein the n value is 10-60, the m value is 0.5-1, and the molar ratio of the dianhydride monomer and triethylamine is 0.8:1.2, preferably 1:1.
[0040] For example, in one embodiment, in steps S1 and S2, the polyamic acid solution is obtained by reacting pyromellitic anhydride, 4,4-diaminodiphenyl ether, triethylamine and 1,3,5-tris(4-aminophenoxy)benzene. The reaction mechanism is shown in the following reaction scheme (I):
[0041]
[0042]
[0043] Furthermore, in the step S3, the polyamic acid salt spinning solution is passed through a metering pump and a spinneret, and is directly sprayed into a coagulation bath by wet spinning, and then washed in a cleaning bath to form the polyamic acid salt hydrogel fiber, and the coagulation bath and the cleaning bath are pure water baths.
[0044] Furthermore, in step S4, the chemical imidization includes placing the polyamic acid salt hydrogel fiber washed with clean water in the organic solvent for 3-4 times of solvent replacement to obtain the polyamic acid salt organogel fiber; and then immersing the polyamic acid salt organogel fiber in an organic solution containing acetic anhydride and pyridine for chemical imidization for 24-48 hours to obtain the polyimide organogel fiber.
[0045] Furthermore, in step S4, the volume ratio of the organic solvent to the polyamic acid salt hydrogel fiber is 5 to 15:1; the molar ratio of the added acetic anhydride and pyridine is 1:1, and the molar ratio of acetic anhydride to the dianhydride monomer of the polyamic acid salt organogel fiber is 2 to 3:1.
[0046] For example, in one embodiment, the reaction mechanism of chemical imidization of amic acid to form imide is shown in the following reaction scheme (II):
[0047]
[0048] Furthermore, in the step S5, the solvent replacement is performed multiple times with ethanol, the volume ratio of ethanol to the polyimide organogel fiber is 5 to 15:1, and then supercritical drying is performed, the supercritical fluid used in the supercritical drying process is supercritical CO2, the pressure is set to 8.5 to 9 MPa, the drying kettle temperature is 40 to 50°C, and the drying time is 12 to 36 hours, preferably 12 to 24 hours;
[0049] Alternatively, the solvent replacement is performed multiple times using a mixed solution of tert-butanol and water, wherein the volume ratio of tert-butanol to water in the mixed solution of tert-butanol and water is 2:3, and the volume ratio of the mixed solution to the polyimide organogel fiber is 5 to 15:1, followed by freeze drying, wherein the temperature during the freeze drying process is -50 to -30°C, the pressure is 1 to 50 Pa, and the drying time is 24 to 72 hours, preferably 24 to 48 hours.
[0050] Compared with the existing polyimide aerogel fibers, the polyimide aerogel fibers of the present invention generate polyamic acid salts by introducing triethylamine and carboxyl groups in polyamic acid in an ionic bond, thereby improving the water solubility of polyamic acid and preventing the fibers from forming a dense film in a pure water coagulation bath, so that pure water can be used as a coagulation bath and a cleaning bath, saving costs while reducing environmental pollution; by introducing a cross-linking agent, the viscosity of the spinning solution is increased and the toughness of the primary fiber is increased, thereby effectively improving the spinnability of the spinning solution, and at the same time reducing the mass fraction of polyamic acid in the spinning solution, so that it has a three-dimensional network structure at the molecular scale, thereby giving the polyimide aerogel fiber good strength and toughness.
[0051] In addition, compared with the existing process, the preparation method of the high-strength polyimide aerogel fiber provided by the present invention has widely available raw materials, a simple preparation process, mild reaction conditions, a controllable reaction process, a continuous process flow, fewer pre- and post-processing steps, and can achieve large-scale production.
[0052] In order to make the purpose, features and advantages of the present invention more obvious and understandable, the high-strength polyimide aerogel fiber and the preparation method thereof according to the embodiments of the present invention are described below through a plurality of non-limiting examples.
[0053] Example
[0054] Example 1
[0055] Take 10.814g (0.1000mol) of the diamine monomer p-phenylenediamine and dissolve it in 450ml of the organic solvent N-methylpyrrolidone. After stirring evenly, take 31.383g (0.1067mol) of the dianhydride monomer 3,3,4,4-biphenyltetracarboxylic dianhydride and add it to the above mixed solution, and stir mechanically in a water bath at room temperature for thirty minutes. After the solution is completely transparent, a polyamic acid solution is obtained. Take 13.900ml (0.1000mol) of triethylamine and add it to the polyamic acid salt solution, and continue stirring for ten minutes. Then take 1.784g (0.0045mol) of the cross-linking agent 1,3,5-tris (4-aminophenoxy) benzene and dissolve it in 50mL N-methylpyrrolidone, add it and continue stirring for ten minutes. Finally, degas under a vacuum environment for 2 hours to obtain a polyamic acid salt spinning solution. The molar ratio of the dianhydride monomer, the diamine monomer, the triethylamine and the crosslinking agent is 16:15:16:0.67. In the polyamic acid salt spinning solution, the mass fraction of the polyamic acid salt is 10.53 wt%.
[0056] During the spinning process, the degassed polyamic acid salt spinning solution is added to a storage tank, which is sealed and pressurized to 1-2 MPa to help the polyamic acid salt spinning solution flow. The polyamic acid salt spinning solution is wet spun. Specifically, a spinneret with a diameter of 0.5 mm is used, and the gap between the spinneret and the coagulation bath water surface is 5 cm, with a spacing of 1.8 cm 3 / min extrusion speed spinning, adjust the frequency of the metering pump and the winding machine, so that the ratio of the winding machine linear speed to the spinning solution linear speed is 2:1. The coagulation bath and the cleaning bath are pure water baths, and the temperature is controlled at 5-15°C. The polyamic acid salt spinning solution is extruded from the spinneret into the coagulation bath by the metering pump, and is solidified by solvent displacement in the coagulation bath to form nascent fibers with a diameter of about 0.35 mm. The nascent fibers are then collected by a guide wheel and a winding machine, and the residual N-methylpyrrolidone on the surface is cleaned in the cleaning bath. The cleaning time is 1 minute, and the solvent displacement is completed to form polyamic acid salt hydrogel fibers.
[0057] Then the polyamic acid salt hydrogel fiber is placed in 10 times its own volume of N-methylpyrrolidone for solvent replacement 4 times, each time for 6 hours, to obtain polyamic acid salt organic gel fiber. The polyamic acid salt organic gel fiber after solvent replacement is immersed in an N-methylpyrrolidone solution with a molar ratio of acetic anhydride to pyridine of 1:1 for 24 hours to obtain polyimide organic gel fiber. The molar ratio of acetic anhydride to the dianhydride monomer of the polyamic acid salt organic gel fiber is 2:1, and the temperature is controlled at 25°C.
[0058] The polyimide organogel fiber is then solvent-exchanged in an ethanol solution 10 times its volume for 4 times, each time for 6 hours, and then subjected to supercritical drying to obtain the polyimide aerogel fiber with a three-dimensional network structure. The supercritical fluid used in the supercritical drying process is supercritical CO2, the drying kettle pressure is controlled at 8.5-9MPa, the drying kettle temperature is controlled at 40-50°C, and the drying time is 15 hours. The obtained polyimide aerogel fiber has a tensile strength of 62.5MPa, an elastic modulus of 821MPa, and a specific surface area of 271m 2 / g, linear density is 23.4tex, thermal conductivity is 0.031W·m -1 ·K -1 .
[0059] Example 2
[0060] Take 20.024g (0.1000mol) of diamine monomer 4,4'-diaminodiphenyl ether and dissolve it in 450ml organic solvent N-methylpyrrolidone. After stirring evenly, take 23.273g (0.1067mol) of dianhydride monomer pyromellitic anhydride and add it to the above mixed solution, and stir mechanically in a water bath at room temperature for thirty minutes. After the solution is completely transparent, a polyamic acid solution is obtained. Take 13.900ml (0.1000mol) of triethylamine and add it to the polyamic acid salt solution, and continue stirring for ten minutes. Then take 1.784g (0.0045mol) of cross-linking agent 1,3,5-tris (4-aminophenoxy) benzene and dissolve it in 50mL N-methylpyrrolidone, add it and continue stirring for ten minutes. Finally, degas under vacuum for 2 hours to obtain a polyamic acid salt spinning solution. The molar ratio of the dianhydride monomer, the diamine monomer, the triethylamine and the crosslinking agent is 16:15:16:0.67. In the polyamic acid salt spinning solution, the mass fraction of the polyamic acid salt is 10.39wt%.
[0061] During the spinning process, the degassed polyamic acid salt spinning solution is added to a storage tank, which is sealed and pressurized to 1-2 MPa to help the polyamic acid salt spinning solution flow. The polyamic acid salt spinning solution is wet spun. Specifically, a spinneret with a diameter of 0.5 mm is used, and the gap between the spinneret and the coagulation bath water surface is 5 cm, with a spacing of 1.8 cm 3 / min extrusion speed spinning, adjust the frequency of the metering pump and the winding machine, so that the ratio of the winding machine linear speed to the spinning solution linear speed is 2:1. The coagulation bath and the cleaning bath are pure water baths, and the temperature is controlled at 5-15°C. The polyamic acid salt spinning solution is extruded from the spinneret into the coagulation bath by the metering pump, and is solidified by solvent displacement in the coagulation bath to form nascent fibers with a diameter of about 0.35 mm. The nascent fibers are then collected by a guide wheel and a winding machine, and the residual N-methylpyrrolidone on the surface is cleaned in the cleaning bath. The cleaning time is 1 minute, and the solvent displacement is completed to form polyamic acid salt hydrogel fibers.
[0062] Then the polyamic acid salt hydrogel fiber is placed in 10 times its own volume of N-methylpyrrolidone for solvent replacement 4 times, each time for 6 hours, to obtain polyamic acid salt organic gel fiber. The polyamic acid salt organic gel fiber after solvent replacement is immersed in an N-methylpyrrolidone solution with a molar ratio of acetic anhydride to pyridine of 1:1 for 24 hours to obtain polyimide organic gel fiber. The molar ratio of acetic anhydride to the dianhydride monomer of the polyamic acid salt organic gel fiber is 2:1, and the temperature is controlled at 25°C.
[0063] The polyimide organogel fiber is then solvent-replaced in a tert-butanol / water solution 10 times its own volume for 4 times, each time for 6 hours, and the volume ratio of tert-butanol / water in the tert-butanol / water solution is 2:3. The polyimide aerogel fiber with a three-dimensional network structure is then obtained by vacuum freeze-drying. During the vacuum freeze-drying process, the temperature is controlled at -50 to -30°C, the pressure is controlled at 1 to 50Pa, and the drying time is 24h. The obtained polyimide aerogel fiber has a tensile strength of 54.5MPa, an elastic modulus of 753MPa, and a specific surface area of 236m 2 / g, linear density 21.3tex, thermal conductivity 0.035W·m -1 ·K -1 .
[0064] Example 3
[0065] Take 20.024g (0.1000mol) of diamine monomer 4,4'-diaminodiphenyl ether and dissolve it in 750ml organic solvent N-methylpyrrolidone. After stirring evenly, take 23.273g (0.1067mol) of dianhydride monomer pyromellitic anhydride and add it to the above mixed solution, and stir mechanically in a normal temperature water bath for thirty minutes. After the solution is completely transparent, a polyamic acid solution is obtained. Take 13.900ml (0.1000mol) of triethylamine and add it to the polyamic acid salt solution, and continue stirring for ten minutes. Then take 1.571g (0.0044mol) of cross-linking agent 1,3,5-tri(4-aminophenyl)benzene and dissolve it in 50mL N-methylpyrrolidone, add it and continue stirring for ten minutes. Finally, degas under vacuum for 2 hours to obtain a polyamic acid salt spinning solution. The molar ratio of the dianhydride monomer, the diamine monomer, the triethylamine and the crosslinking agent is 16:15:16:0.67. In the polyamic acid salt spinning solution, the mass fraction of the polyamic acid salt is 6.69wt%.
[0066] During the spinning process, the degassed polyamic acid salt spinning solution is added to a storage tank, which is sealed and pressurized to 1-2 MPa to help the polyamic acid salt spinning solution flow. The polyamic acid salt spinning solution is wet spun. Specifically, a spinneret with a diameter of 0.5 mm is used, and the gap between the spinneret and the coagulation bath water surface is 5 cm, with a spacing of 1.8 cm 3 / min extrusion speed spinning, adjust the frequency of the metering pump and the winding machine, so that the ratio of the winding machine linear speed to the spinning solution linear speed is 2:1. The coagulation bath and the cleaning bath are pure water baths, and the temperature is controlled at 5-15°C. The polyamic acid salt spinning solution is extruded from the spinneret into the coagulation bath by the metering pump, and is solidified by solvent displacement in the coagulation bath to form nascent fibers with a diameter of about 0.35 mm. The nascent fibers are then collected by a guide wheel and a winding machine, and the residual N-methylpyrrolidone on the surface is cleaned in the cleaning bath. The cleaning time is 1 minute, and the solvent displacement is completed to form polyamic acid salt hydrogel fibers.
[0067] Then the polyamic acid salt hydrogel fiber is placed in 10 times its own volume of N-methylpyrrolidone for solvent replacement 4 times, each time for 6 hours, to obtain polyamic acid salt organic gel fiber. The polyamic acid salt organic gel fiber after solvent replacement is immersed in an N-methylpyrrolidone solution with a molar ratio of acetic anhydride to pyridine of 1:1 for 24 hours to obtain polyimide organic gel fiber. The molar ratio of acetic anhydride to the dianhydride monomer of the polyamic acid salt organic gel fiber is 2:1, and the temperature is controlled at 25°C.
[0068] The polyimide organogel fiber is then solvent-exchanged in an ethanol solution 10 times its volume for 4 times, each time for 6 hours, and then subjected to supercritical drying to obtain the polyimide aerogel fiber with a three-dimensional network structure. The supercritical fluid used in the supercritical drying process is supercritical CO2, the drying kettle pressure is controlled at 8.5-9MPa, the drying kettle temperature is controlled at 40-50°C, and the drying time is 16 hours. The obtained polyimide aerogel fiber has a tensile strength of 46.5MPa, an elastic modulus of 634MPa, and a specific surface area of 283m 2 / g, linear density is 19.1tex, thermal conductivity is 0.033W·m-1·K -1 .
[0069] Although at least one embodiment has been provided in the foregoing detailed description, it should be understood that there are a large number of variations. It should also be understood that these embodiments are merely exemplary and are not intended to limit the scope of the invention in any way. On the contrary, the foregoing detailed description will provide a convenient roadmap for implementing an embodiment of the invention for those skilled in the art. It should be understood that, without departing from the scope of the invention as set forth in the attached claims and their legal equivalents, various changes may be made to the function and arrangement of the elements described in the exemplary embodiments.
Claims
1. A method for preparing high-strength polyimide aerogel fiber, characterized in that: The steps include: Step S1, preparing a polyamic acid solution at room temperature; Step S2, performing a pre-spinning treatment on the polyamic acid solution, comprising: Step S21, adding triethylamine to the polyamic acid solution to adjust the water solubility of the spinning solution; Step S22, adding a crosslinking agent to the solution after step S21 to improve the spinnability of the spinning solution; and Step S23, performing vacuum degassing treatment on the solution after step S22 to obtain a polyamic acid salt spinning solution; Step S3, spinning the polyamic acid salt spinning solution to obtain polyamic acid salt hydrogel fibers; Step S4, performing solvent replacement on the polyamic acid salt hydrogel fiber to obtain polyamic acid salt organogel fiber, and then performing chemical imidization in solution to obtain polyimide organogel fiber; and Step S5, performing solvent replacement on the polyimide organogel fiber, and then freeze-drying or supercritical drying in a drying kettle to obtain the polyimide aerogel fiber, In the step S1, the polyamic acid solution is formed by polymerizing a dianhydride monomer and a diamine monomer in an organic solvent; The dianhydride monomer is one or more selected from biphenyltetracarboxylic dianhydride, diphenyl ether tetracarboxylic dianhydride, benzophenone tetracarboxylic anhydride, bisphenol A dianhydride, oxydiphthalic anhydride, biphenyltetracarboxylic dianhydride, and pyromellitic anhydride; The diamine monomer is one or more selected from 4,4'-diaminodiphenyl ether, p-phenylenediamine, diphenylmethane diisocyanate, toluene diisocyanate, 4,4'-diaminobenzanilide, 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl, 2,2'-bis[4-(4-aminophenoxyphenyl)]propane, and bis(4-aminophenoxy)benzene; The organic solvent is one selected from N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide and dimethylacetamide.
2. The preparation method according to claim 1, characterized in that: The cross-linking agent is one or more selected from 1,3,5-tris(4-aminophenoxy)benzene, bis[3-(trimethoxysilyl)propyl]amine, N1,N3,N5 tris(4-aminophenyl)benzene-1,3,5-tricarboxamide, tris(4-aminophenyl)amine, 2,4,6-tris(4-aminophenoxy)-1,3,5-triazine, 1,3,5-tris(4-aminophenyl)benzene, and melamine.
3. The preparation method according to claim 1, characterized in that: In the polyamic acid salt spinning solution, the mass concentration of polyamic acid salt is 5-15wt%, the molar ratio of the dianhydride monomer, the diamine monomer and the crosslinking agent is (n+1) / n / m, wherein the n value is 10-60, the m value is 0.5-1, and the molar ratio of the dianhydride monomer to triethylamine is 0.8:1.
2.
4. The preparation method according to claim 1, characterized in that: In the step S3, the polyamic acid salt spinning solution is directly sprayed into a coagulation bath through a metering pump and a spinneret by wet spinning, and then washed in a cleaning bath to form the polyamic acid salt hydrogel fiber, and the coagulation bath and the cleaning bath are pure water baths.
5. The preparation method according to claim 1, characterized in that: In step S4, the chemical imidization includes placing the polyamic acid salt hydrogel fiber washed with clean water in an organic solvent for 3-4 times of solvent replacement to obtain the polyamic acid salt organogel fiber; then immersing the polyamic acid salt organogel fiber in an organic solution containing acetic anhydride and pyridine for chemical imidization for 24-48 hours to obtain the polyimide organogel fiber.
6. According to the preparation method of claim 5, the volume ratio of the organic solvent to the polyamic acid salt hydrogel fiber is 5 to 15:1; the molar ratio of the added acetic anhydride and pyridine is 1:1, and the molar ratio of acetic anhydride to the dianhydride monomer of the polyamic acid salt organogel fiber is 2 to 3:
1.
7. The preparation method according to claim 1, characterized in that: In the step S5, the solvent replacement is performed multiple times with ethanol, and the volume ratio of ethanol to the polyimide organogel fiber is 5 to 15:
1. Thereafter, supercritical drying is performed, and the supercritical fluid used in the supercritical drying process is supercritical CO2, the pressure is set to 8.5 to 9 MPa, the drying kettle temperature is 40 to 50°C, and the drying time is 12 to 24 hours.
8. The preparation method according to claim 1, characterized in that: In the step S5, the solvent replacement is performed multiple times using a mixed solution of tert-butanol and water, the volume ratio of tert-butanol to water in the mixed solution of tert-butanol and water is 2:3, and the volume ratio of the mixed solution to the polyimide organogel fiber is 5 to 15:1, followed by freeze drying, wherein the temperature during the freeze drying process is -50 to -30°C, the pressure is 1 to 50 Pa, and the drying time is 24 to 48 hours.
9. The high-strength polyimide aerogel fiber prepared by the preparation method according to any one of claims 1 to 8, characterized in that The polyimide aerogel fiber has a three-dimensional network structure formed by cross-linking polyimide nanofibers. The polyimide aerogel fiber has a tensile strength of 20-100 MPa, an elastic modulus of 800-1400 MPa, and a specific surface area of 100-300 m 2 / g, linear density is 15-25tex, thermal conductivity is 0.02-0.07W·m -1 ·K -1 , and has good spinnability.
Citation Information
Patent Citations
Polyimide aerogel fiber as well as preparation and application thereof
CN111808283A
Polyimide aerogel fiber and preparation method thereof
CN113403707A